2012
DOI: 10.1021/am300144w
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponsive Polymer Conetworks Capable of Responding to Changes in pH, Temperature, and Magnetic Field: Synthesis, Characterization, and Evaluation of Their Ability for Controlled Uptake and Release of Solutes

Abstract: This study deals with the preparation of novel multiresponsive (magnetoresponsive, thermoresponsive and pH-responsive) nanocomposite conetworks consisting of oleic acid-coated magnetite nanoparticles (OA·Fe(3)O(4)), hydrophilic/thermoresponsive hexa(ethylene glycol) methyl ether methacrylate (HEGMA), hydrophobic/metal binding 2-(acetoacetoxy)ethyl methacrylate (AEMA), and pH-responsive/thermoresponsive N-diethylaminoethyl methacrylate (DEAEMA) and 2-(dimethylamino)ethyl methacrylate (DMAEMA) moieties. Conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…These systems were evaluated toward their ability to absorb and release benzoic acid as a model drug in a controlled manner upon varying the pH. 63 Hezaveh et al synthesized NC gels from modified kappa-carrageenan and MgO nanoparticle, methylene blue was used as the model drug to investigate. It was found that the amount of methylene blue released from NC gel can be 67.5% higher in intestine medium and 56% lower in the stomach compared to kappa-carrageenan hydrogel.…”
Section: Application Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…These systems were evaluated toward their ability to absorb and release benzoic acid as a model drug in a controlled manner upon varying the pH. 63 Hezaveh et al synthesized NC gels from modified kappa-carrageenan and MgO nanoparticle, methylene blue was used as the model drug to investigate. It was found that the amount of methylene blue released from NC gel can be 67.5% higher in intestine medium and 56% lower in the stomach compared to kappa-carrageenan hydrogel.…”
Section: Application Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…A hydrophobic and a hydrophilic dye were encapsulated and released to order to prove that the amphiphilic nature of the AA-EGDMA microgels could be utilised for the capture and delivery of moieties of varying hydrophobicity/hydrophilicity, similarly to amphiphilic macrogels 41,42 . The release of the model drugs were trigged by making the pH of the environment basic such that the AA units became ionised and the microgels swelled, allowing the dyes to diffuse out.…”
Section: Dye Encapsulation and Release Studiesmentioning
confidence: 99%
“…Also, magnetite nanoparticles chemically modified with citric acid and trisodium citrate have shown superparamagnetic behavior. In order to obtain better stability other processes have been adapted to produce changes on the magnetite surface using carboxylic or other linking groups with different polymers such as polyethylene glycol (PEG) 4,[27][28][29] , diethylene glycol 30 , polymethyl acrylates (PMMA, HEGMA or AEMA) 31,32 , poly(lactic-co-glycolic acid) (PLGA) 33 . However, the magnetite nanoparticles stabilization processes can induce surface oxidation due to changes in pH or temperature.…”
mentioning
confidence: 99%